Screening for interstitial lung disease in systemic sclerosis: performance of high-resolution CT with limited number of slices: a prospective study. Issue 12 (30th September 2014) - Frauenfelder, Thomas; Winklehner, Anna; Nguyen, Thi Dan Linh; Dobrota, Rucsandra; Baumueller, Stephan; Maurer, Britta; Distler, Oliver
Abstract : Objectives: Early diagnosis of interstitial lung disease (ILD), currently the main cause of death in systemic sclerosis (SSc), is needed. The gold standard is high-resolution CT (HRCT) of the chest, but regular screening faces the risk of increased radiation exposure. We performed a prospective validation of a dedicated, 9-slice HRCT protocol with reduced radiation dose for the detection of ILD in patients with SSc. Methods: We analysed 170/205 consecutive patients with SSc. Whole-chest HRCT, serving as standard of reference, and the reduced HRCT with nine slices allocated according to a basal–apical gradient were obtained. ILD presence, extent (> or <20%) and diagnostic confidence were assessed. The reduced HRCT was independently analysed by two blinded radiologists, who also evaluated image quality. Radiation dose parameters were calculated. Results: Standard chest HRCT showed ILD in 77/170 patients. With the reduced HRCT, 68/77 cases with ILD were identified (sensitivity 88.3%, both readers). The accuracy (91.8%, reader 1; 94.7%, reader 2), diagnostic confidence (98.8%, reader 1; 95.3%, reader 2) and image quality rates were high. Minimal ILD was correctly quantified in 73.1% (reader 1)/71.2% (reader 2) and extensive ILD in 88% (reader 1)/100% (reader 2). Importantly, the reduced HRCT had a significantly lower radiation dose. The mean dose length product (effective dose) was only 5.66±4.46 mGycm (0.08±0.06 mSv) compared with the standard protocol dose of 149.00±95.90 mGycm (2.09±1.34 mSv). Conclusions: The above-described reduced chest HRCT protocol reliably detects even mild SSc-ILD in clinical practice, with the advantage of a much lower radiation dose compared with standard whole-chest HRCT.